CHALLENGES AND FUTURES OF UBIQUITOUS LEARNING IN TEACHING ENGLISH AS A FOREIGH LANGUAGE - Suhartatik; Hernina Dewi Lestari (UIBU, 2022)
This research aims at analyzing the challenges and the potential futures of the implementation of ubiquitous learning in teaching English as a foreign language (TEFL) in Indonesian context. This study employed descriptive qualitative research design with observation and interview as the data collection techniques. The samples of this research participants were 50 bachelor degree students majoring in English Education who were chosen through random sampling technique. After the data were attained, they were analyzed to answer the research questions of what challenges and futures of ubiquitous learning in Indonesian TEFL context were. The research findings presented that three major challenges in the implementation of ubiquitous learning in TEFL were technical problems (internet connection-related problems) which took 50% of the concerns, devices operating competence which had 30% of the attentions, and students’ attitude which had 20% of the problems. About the futures of ubiquitous learning in TEFL context, the participants testified that ubiquitous learning could be an excellent alternative to study from anywhere and at any time (40%), 30% suggested technical readiness to optimize the learning outcome, the other 20% thought that Indonesian students were not ready for the implementation of ubiquitous learning, and another 10% stayed neutral to the option. These findings contribute to fill the gap of the controversies of ubiquitous learning implementation. It is suggested that future researchers took deeper examination related to this topic.